2015
DOI: 10.1038/srep12474
|View full text |Cite
|
Sign up to set email alerts
|

Computational Classification Approach to Profile Neuron Subtypes from Brain Activity Mapping Data

Abstract: The analysis of cell type-specific activity patterns during behaviors is important for better understanding of how neural circuits generate cognition, but has not been well explored from in vivo neurophysiological datasets. Here, we describe a computational approach to uncover distinct cell subpopulations from in vivo neural spike datasets. This method, termed “inter-spike-interval classification-analysis” (ISICA), is comprised of four major steps: spike pattern feature-extraction, pre-clustering analysis, clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…For example, multi-phasic temporal dynamics in DAergic neurons have been reported in studies using unexpected (unconditioned) aversive stimuli ( 40 , 53 ). Consistent with such complex dynamics, we recently described computational classifications of DAergic subtypes based on their distinct inter-spike-interval dynamics ( 54 ). Such classifications were further verified by optogenetic methods ( 54 ).…”
Section: Da Circuit Diversity and Complexitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, multi-phasic temporal dynamics in DAergic neurons have been reported in studies using unexpected (unconditioned) aversive stimuli ( 40 , 53 ). Consistent with such complex dynamics, we recently described computational classifications of DAergic subtypes based on their distinct inter-spike-interval dynamics ( 54 ). Such classifications were further verified by optogenetic methods ( 54 ).…”
Section: Da Circuit Diversity and Complexitymentioning
confidence: 99%
“…Consistent with such complex dynamics, we recently described computational classifications of DAergic subtypes based on their distinct inter-spike-interval dynamics ( 54 ). Such classifications were further verified by optogenetic methods ( 54 ). In addition, downstream targets receiving DAergic projections can send feedback projections to modulate DA activities ( 55 57 ).…”
Section: Da Circuit Diversity and Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…To further evaluate the general utility of the gamma distribution model, we then analyzed neuromodulatory projection neurons, such as dopaminergic (DA) neurons recorded from the mouse VTA region. The DA neuron dataset was collected from freelybehaving mice during the awake period as we have previously described [27,38]. DA The line in the plot denotes the linear regression between D and mean firing rates.…”
Section: Spike-timing Patterns Of Vta Dopaminergic Neurons Conformed mentioning
confidence: 99%
“…It has been shown that in spite of "channel noise" [9], deterministic neuronal models can accurately predict stimulus responses [15].The irregularity of inter-spike intervals has long been suggested to be a fundamental process of cortical communication [6,[16][17][18][19][20], and it was often modeled as a Poisson-like random process. Intriguingly, a growing number of observations have shown that the neuronal spike pattern in many cortical areas seems to be inconsistent with the Poisson process, indicating that the Poisson process can either under-or overestimate the variabilities of the neuronal spike patterns [21][22][23][24][25][26][27][28]. Despite the importance in regulating synaptic plasticity and neural coding, spike-time patterns across a wide range of brain regions and animal species have not been examined or compared in a systematic manner.…”
mentioning
confidence: 99%